Limb asymmetries persist 6 months after anterior cruciate ligament reconstruction according to the results of a jump test battery - Legnani, Claudio; Del Re, Matteo; Peretti, Giuseppe M.; Borgo, Enrico; Macchi, Vittorio; Ventura, Alberto (Frontiers in Medicine, 2024)
Objectives: A simple standardized jump test battery was developed to objectively evaluate knee function following ACLR, thereby aiding in RTS decision-making. Methods: Thirty-three patients who underwent ACLR were prospectively assessed pre-operatively, 6, and 12 months after surgery. Knee function was assessed using a device for optical detection using a test battery consisting of three jump tests: monopodalic countermovement jump (CMJ), drop jump, and monopodalic side-hop. Limb symmetry index (LSI) was reported for all tests at all time points. LSI ≥90% was defined as RTS criteria. Results: At 12-month evaluation, mean LSI significantly improved compared to 6-month follow up (p<0.01), and also compared to baseline (p<0.01), reporting a mean value of 92.6% for CMJ, 90.6 for drop jump and 96.9% for side hop test. Most patients fulfilled the RTS criteria 12 months after surgery (LSI ≥90%). The percentages of patients demonstrating LSI ≥90% at 6 months was 7/33 (21.2%) for CMJ, 12/33 (36.4%) for drop jump, and 11/33 (33.3%) for side-hop test. One year after surgery, percentages grew up to 66.6% (22/33), 63.6% (21/33), and 81.8% (27/33) respectively. Conclusions: Six months after ACLR, knee functional performance was unsatisfactory in most patients, whereas a significantly higher percentage of patients met RTS criteria one year after surgery. The results of the jump test battery proposed in this study support the idea that timing for resumption of cutting and pivoting sports should be delayed later than 6 months, as still limb asymmetries persist at this time point.